Análise de fluoxetina e norfluoxetina em plasma por microextração em fase líquida e GC-MS com derivatização no injetor - Oliveira, Antônio Felipe Felicioni (2011)
Fluoxetine (FLU) is a widely prescribed antidepressant for major depression and other neurological diseases. In addition to the unchanged form, its metabolite – norfluoxetine (NOR) – also has pharmacological activity. Determination of FLU in biofluids is necessary in therapeutic drug monitoring (TDM), in new formulation development, as well as in analytical and forensic toxicology. Miniaturized techniques such as LPME have been used in biological sample preparation, being simple, sensitive, and environmentally friendly. Liquid chromatography is considered the technique of choice for the analysis of FLU and NOR, because in its underivatized form these compounds are incompatible with gas chromatography (GC); which would be of interest for its simplicity and low cost. This work presents the development of a method for FLU and NOR analysis in plasma by LPME-GC-MS using injection-port derivatization (IPD). The process made these drugs suitable for analysis, being the online procedure promising due to low derivatizing agent consumption, as well as not adding steps in sample preparation. Polypropylene hollow-fibers (600 μm inside diameter, 200 μm wall thickness, and 0.2 μm pore size) were used for extraction and analyses were performed in a GC-MS 2010 Plus Shimadzu®. One microliter of derivatizing agent MBTFA (n-methyl-bis trifluoroacetamide) and 2 μL of extract were directly injected into the GC port. The IPD process was optimized for carrier gas flow rate, injector and column temperature, high-pressure injection mode (HPI), and type of insert liner. The extraction was evaluated for salting out effect, donor phase pH, and plasma proteins precipitation; additionally, two factorial designs were performed to verify the influence of thermodynamic parameters (type and volume of solvent, buffer concentration and dilution of the sample), and of kinetic parameters (extraction time and stirring speed) on extraction. For the IPD were optimized a flow rate of 1.7 mL/min, an injector temperature of 300 °C and a column initial temperature of 140 °C, using HPI at 250 kPa and split liner. Using the optimized chromatographic conditions and nortriptyline as the internal standard the proposed method was: 1 mL of plasma after protein precipitation with ZnSO4/NaOH, 4 mL of 0.1 mol/L phosphate buffer at pH 11. Hollow-fiber pieces of 3.7 cm with 10 μL of dihexyl ether for 30 min at 700 rpm were used for extraction. Linearity for FLU was between 10 and 500 ng/mL (R2 = 0.9973), and for NOR between 15 and 500 ng/mL (R2 = 0.9972). Detection and quantification limits of 3 and 10 ng/mL, and of 5 and 15 ng/mL for FLU and NOR, respectively. The intra-assay and inter-assay precision and accuracy were studied for three concentrations (50, 250 e 500 ng/mL). Selectivity, short term stability and extraction efficiency were also evaluated. After validated the method was successfully applied to the analysis of samples from 5 patients under fluoxetine treatment The developed method is fast, sensible and environmentally friendly, significantly reducing both the use of solvents in sample preparation and separation. The IPD with MBTFA, unpublished until the moment for the GC analysis of drugs, has been showing promising results and may be used as an alternative to HPLC analysis.